THE TRACER STUDY: AN IN-DEPTH SEARCH OF THE ENGLISH EDUCATION PROGRAM GRADUATES - Silih Warni; Cahya Komara; Nita Kaniadewi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Universities have an important role in generating amazing alums who can compete with others. This role makes universities try to find a way to increase the alums' quality. One of them is the tracer study. Tracer study is a technique to track the alums' quality. Therefore, the research objective was to investigate the status, quality, and accomplishment of the graduates/alums of the English Education Program of FKIP UHAMKA. This research employed a mixed-method sequential explanatory research design which combined quantitative and qualitative research design. As many as 98 graduates from the English Education Program participated in the study. A questionnaire that was validated using a validity test before it was distributed through several social media was used as the instrument of this study. Findings have discovered that most of the graduates of the English Education Program who graduated in 2021 can implement their knowledge and abilities per the field of education they had on campus. Unfortunately, graduates whose jobs were in line with their field of study still got low payment. Further research is needed to evaluate the competencies and training that need to be accommodated by the campus to prepare upcoming alums before entering the workspace.